BIOCHEMICAL AND ULTRASTRUCTURAL PROPERTIES OF A MITOCHONDRIAL INNER MEMBRANE FRACTION DEFICIENT IN OUTER MEMBRANE AND MATRIX ACTIVITIES - Chan, T. L. (The Rockefeller University Press, 1970)
Treatment of the inner membrane matrix fraction of rat liver mitochondria with the nonionic detergent Lubrol WX solubilized about 70% of the total protein and 90% or more of the following matrix activities: malate dehydrogenase, glutamate dehydrogenase, and isocitrate dehydrogenase (NADP). The Lubrol-insoluble fraction was enriched in cytochromes, phospholipids, and a Mg(++)-stimulated ATPase activity. Less than 2% of the total mitochondrial activity of monoamine oxidase, an outer membrane marker, or adenylate kinase, an intracristal space marker could be detected in this inner membrane fraction. Electron micrographs of negatively stained preparations showed vesicles (≤0.4 µ diameter) literally saturated on the periphery with the 90 A ATPase particles. These inner membrane vesicles, which appeared for the most part to be inverted with respect to the normal inner membrane configuration in intact mitochondria, retained the succinicoxidase portion of the electron-transport chain, an intact phosphorylation site II with a high affinity for ADP, and the capacity to accumulate Ca(++). A number of biochemical properties characteristic of intact mitochondria and the inner membrane matrix fraction, however, were either absent or markedly deficient in the inner membrane vesicles. These included stimulation of respiration by either ADP or 2,4-dinitrophenol, oligomycin-sensitive ADP-ATP exchange activity, atractyloside sensitivity of adenine nucleotide requiring reactions, and a stimulation of the Mg(++)-ATPase by 2,4-dinitrophenol.